The effect of pain intensity levels and clinical symptoms on the treatment preferences of patients with endodontically involved teeth: A preliminary cross-sectional study - Eyüboğlu, Tan Fırat; İlçin Gönenç, Fulya (Istanbul University Press, 2020)
PurposeThis study aimed to evaluate the effect of pain intensity levels and clinical symptoms on the treatment preferences of patients with endodontically involved teeth in a local Turkish population.Subjects and MethodsA total of 30 patients with symptomatic teeth requiring non-surgical root canal treatment were included in the study. The patients' demographic (age, gender, and education level) and diagnostic data (tooth type, pain intensity, response to percussion and palpation, presence of referred pain, and diagnosis) were analyzed. Data on the patients' explicit preferences (requested treatment, whether they are willing to accept a proposed extraction, choice of treatment if an anterior tooth was involved, and choice of treatment if the pain was not severe) as well as previous root canal treatment experiences were also analyzed. Pain intensity levels were evaluated using the Visual Analog Scale.ResultsPain intensity levels had a significant effect on the treatment requested by the patient (p=0.001). Among the patients who requested extraction upon referral to the clinic, the rate of those who reported that they would not accept extraction if the pain was located in an anterior tooth was significantly lower than that of patients stating that they would refuse (p=0.039). The presence of referred pain also had a significant effect on the requested treatment (p=0.001).ConclusionThe intensity of pain and the presence of referred pain influence patients' treatment preferences.
Keywords: Decision-Making; Dental Pain; Ethics; Informed Consent; Treatment Preference